Penalaran Proporsional Siswa SMP Islam Bani Hasyim Singosari Dalam Menyelesaikan Soal Perbandingan Terintegrasi Islam - Farha Ashiilah Herwinsyah; Ulfa Masamah (Galois: Jurnal Penelitian Pendidikan Matematika, 2026)
This study discusses the analysis of proportional reasoning ability of students at SMP Islam Bani Hasyim Singosari in solving comparison problems integrated with Islamic values. The main issue examined is the low ability of students to understand proportional concepts. The research aims to analyze students' proportional reasoning skills, particularly in solving comparison problems within the Islamic context, specifically zakat. The method used is qualitative descriptive research with data collected through written tests and structured interviews with purposively selected students. Data analysis was conducted using triangulation techniques to obtain a comprehensive picture of students’ proportional reasoning abilities. The results indicate that most students meet the indicators of proportional reasoning, namely understanding the concept of covariation, identifying proportional situations, and correctly using multiplicative strategies. However, there are still limitations in accurately understanding the conditions for ratio usage and integrating the concept of zakat within the problem context. Thus, the study confirms that mathematics learning that optimally integrates Islamic values has the potential to strengthen mastery of the material and foster students' religious attitudes in a balanced manner.